2014
DOI: 10.1128/jvi.02702-13
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Detection by the cGAS/STING/TBK1 DNA Sensing Cascade

Abstract: T he human serotype 5 adenovirus (Ad5) is a nonenveloped linear double-stranded DNA virus associated with upper respiratory tract disease in humans. It has been extensively studied as a model for virus and host cell interactions. Replication-defective recombinant Ad5 vectors (rAdV) deleted in E1 and E3 coding domains have been characterized in gene therapy, vaccine, and oncolytic vector strategies in the murine model. Although nonpermissive for Ad5 replication, the murine model of rAdV infection provides a val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
159
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(167 citation statements)
references
References 49 publications
6
159
1
1
Order By: Relevance
“…The cGAS/STING/TBK-1 pathway is capable of sensing cytoplasmic AdV DNA, leading to IRF3 activation (50,51). In our studies, however, infection with 1,000 PFU/ cell of AdV particles failed to elicit a response (data not shown), while infection with 0.02 PFU/cell of HCMV particles efficiently induced a response.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…The cGAS/STING/TBK-1 pathway is capable of sensing cytoplasmic AdV DNA, leading to IRF3 activation (50,51). In our studies, however, infection with 1,000 PFU/ cell of AdV particles failed to elicit a response (data not shown), while infection with 0.02 PFU/cell of HCMV particles efficiently induced a response.…”
Section: Discussioncontrasting
confidence: 46%
“…For example, VLPs and fusogenic liposomes efficiently induce type I IFN and ISGs in human immune cells (22). Similarly, AdV activates the cGAS/STING pathway and elicits IRF3 activation in murine macrophages (50,51), while AdV infection of primary mouse lung fibroblasts leads to type I IFN induction (55). Our studies also highlight the exquisite sensitivity of cells to incoming lowlevel virus particle entry.…”
Section: Discussionmentioning
confidence: 77%
“…Indeed for rAd5 and chAd63, the IFN-driven gene expression profile was abrogated entirely in the absence of STING, leading us to hypothesize that STING acts as a proximal and dominant PRR after vaccination with certain rAds. STING likely senses rAd-derived DNA exposed as the viral particles uncoat in transfected cells (37,38,(41)(42)(43). We speculate that accessibility of rAd-derived DNA to DNA sensors may differ due to different uncoating processes across adenoviral serotypes, leading to differential ISG induction observed in our study.…”
Section: Discussionmentioning
confidence: 65%
“…This suggests that high and persistent Ag expression by rAd5 and chAd3 may not only result from attenuated IFN induction by these vectors but also from specific and positive regulation vated by cytosolic DNA via the action of DNA sensors, such as cyclic GMP-AMP synthase (37-39), or directly activated by bacterially generated cyclic dinucleotides (39,40) and may detect viral fusion events (41). Recent in vitro studies have shown that STING activates innate pathways after adenoviral infection (42,43) and mediates a key innate signaling pathway for sensing a variety of viruses with dsDNA or RNA genomes (44). Mice were vaccinated with rAd5 or chAd63 at a low dose (3 × 10 7 PU) to focus on innate regulation of CD8 T cell responses in the context of more limiting Ag, as high doses of rAds can mask the influence of innate pathways in mice (18,19).…”
Section: Abrogation Of Type I Ifn Signaling Increases Ag Expression Amentioning
confidence: 99%
“…Although adaptive immune responses following administration with Ad vectors has been relatively well studied [3], the mechanisms underlying Ad-induced innate immune responses have remained to be clarified. Several groups, including ours, have reported that Ad components, including capsid proteins, Ad genome DNA, and transcripts, are recognized by cellular receptors and sensors, leading to the induction of innate immune responses [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%